2022
DOI: 10.6007/ijarped/v11-i4/15869
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Learning Styles and Academic Performance of Biology Students

Abstract: Learning style has its insightful impact on the particular dimensions of teaching and learning process. Students have their own preferred way to recognize, retain and retrieve information to perform well in academic performance. The purpose of this study is to determine the students' preference learning styles and the correlation between students' academic performance among biology students in one of public universities in Malaysia. A descriptive research design was employed using survey method to analyse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Tactile learners may struggle with abstract or theoretical concepts without concrete and tangible experiences [6]. They tend to be very hands-on and prefer to learn through active exploration of real-world objects and materials (experimentation) [14] and [36]. Tactile learners may become easily bored or disengaged during passive or lecture-based instruction and may benefit from opportunities to interact with the material in a more physical or tactile way [6].…”
Section: Characteristics Of Tactile Learnersmentioning
confidence: 99%
See 2 more Smart Citations
“…Tactile learners may struggle with abstract or theoretical concepts without concrete and tangible experiences [6]. They tend to be very hands-on and prefer to learn through active exploration of real-world objects and materials (experimentation) [14] and [36]. Tactile learners may become easily bored or disengaged during passive or lecture-based instruction and may benefit from opportunities to interact with the material in a more physical or tactile way [6].…”
Section: Characteristics Of Tactile Learnersmentioning
confidence: 99%
“…Hands-on Laboratory Activities: Studies like [23] have shown that incorporating hands-on laboratory activities into secondary school biology instruction improved students' understanding of biological concepts and increased their motivation to learn. This allow students to manipulate materials [14] and engage in active learning.…”
Section: Strategies For Incorporating Tactile Learning In Biology Ins...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a significant gap persists between the pedagogical strategies employed in construction technology education and the diverse needs of students entering this field. This gap is where the crucial intersection of effective teaching and learning styles assessment comes into play (Ibrahim and Zulkipli, 2022). The need to bridge this gap has never been more pressing, and in this research, the comprehensive exploration is anchored in the pioneering works of Fleming and his VARK model (Visual, Auditory, Reading/Writing, and Kinesthetic), a widely recognized framework for understanding and assessing diverse learning styles.…”
Section: Introductionmentioning
confidence: 99%